2020
DOI: 10.32872/spb.2875
|View full text |Cite
|
Sign up to set email alerts
|

Motivational and affective drivers of right-wing populism support: Insights from an Austrian presidential election

Abstract: Research has identified political disenchantment as an important driver for the recent spread of right-wing populism. The cultural backlash approach explains this relationship as a counter response to progressive socio-political developments in Western societies. Drawing on previous work, the present research examines motivational and affective factors underlying the support of right-wing populist parties. We hypothesize that a perceived alienation from the symbolic architecture of a society may decrease level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…For example, people with more individualistic worldviews are more likely to oppose vaccinations programs and dismiss climate change prevention policies-despite the scientific evidence that they benefit both individuals and collectivesbecause of the perceived associations with government control (Ballew et al, 2020;Hornsey et al, 2018). Thus, the current research also complements research aimed at understanding opposition to collectively beneficial government policies (see implications below) insomuch as dissatisfaction with one's relationships offers a potential mechanism that may explain how people become more individualistically and populistically oriented over time (Huang et al, 2020;Lüders et al, 2020;Reis, 2012;Torcal, 2014).…”
Section: Discussionmentioning
confidence: 81%
“…For example, people with more individualistic worldviews are more likely to oppose vaccinations programs and dismiss climate change prevention policies-despite the scientific evidence that they benefit both individuals and collectivesbecause of the perceived associations with government control (Ballew et al, 2020;Hornsey et al, 2018). Thus, the current research also complements research aimed at understanding opposition to collectively beneficial government policies (see implications below) insomuch as dissatisfaction with one's relationships offers a potential mechanism that may explain how people become more individualistically and populistically oriented over time (Huang et al, 2020;Lüders et al, 2020;Reis, 2012;Torcal, 2014).…”
Section: Discussionmentioning
confidence: 81%
“…right-wing populism in many Western democracies (Lüders et al, 2020). Other analyses highlighting the roles of disinformation, conspiracy theories (DiGrazia, 2017;Sawyer, 2020Sawyer, , 2021, and conspiratorial thinking (van der Linden et al, 2021) are bolstered by the continued belief among many Americans that Donald Trump won the 2020 presidential election, that the election was stolen, and that he would be reinstated as president in the coming months.…”
mentioning
confidence: 99%
“…Appraisal research in psychology has largely been inattentive to research published elsewhere showing robust interactions between fear and diminished reliance on otherwise influential dispositions (Marcus and MacKuen, 1993;Marcus et al, 2000;Brader, 2005Brader, , 2006Valentino et al, 2008) and that anger also has a robust interaction in enhancing political action (Valentino et al, 2011). In addition, research on anger shows a robust effect of angerenhancing reliance on extant dispositions and blocking attention to contrary information and sources (Webster and Abramowitz, 2017;Suhay and Erisen, 2018;Vasilopoulos et al, 2019;Lüders et al, 2020). Much of this research is published in political science.…”
Section: Causal Claimsmentioning
confidence: 99%
“…This differs from other appraisal theories that select an emotion word, presume it to be an actual emotion, and further presume that it can be properly studied in isolation from other emotions (Close and van Haute, 2020;Capelos et al, 2021;Coifman et al, 2021). Validation of the AIT taxonomy rests on research on the neural systems that subserve each of the identified preconscious emotion channels (Gray, 1987;Calder et al, 2001;Rolls, 2014;Caruana, 2017;Celeghin et al, 2017;Lüders et al, 2020).…”
Section: Causal Claimsmentioning
confidence: 99%